Factors that Impact Infidelity Forgiveness - Bradford, Ruby (East Carolina University, 2023)
Each romantic relationship has unique qualities and circumstances. However, there are ways to predict the behaviors that people engage in while in these companionships. Carol Dweck's Mindset theory has many domains that it can be applied to, however in this paper the focus is romance. This paper reviews relevant literature and the completed undergraduate study that examined the connection between the two implicit theories, growth and destiny, and its impact on people's willingness to forgive. In this study infidelity is split into four subtypes: emotional, online/technology, sexual/explicit, and solitary. After replicating the methods of Thompson et al. (2020) with recruited PSYC1000 students and using additional priming techniques, we assessed the similarities and differences between the results of the previous study and the current study. We found that the priming techniques, a short article and reflection questions, were not successful in enforcing either of the implicit theories. These findings were not consistent with Thompson et al. (2020). However, in line with the previous study, women were less likely than men to forgive all subtypes of infidelity. Also, among all participants, the most forgivable subtype was solitary infidelity and the least forgivable was sexual/explicit infidelity.
Keywords: Implicit theories; romance; infidelity; forgiveness; decks mindset theory